The determination of titratable acidity and total tannins in red wine - Rajković Miloš B.; Sredović Ivana D. (Journal of Agricultural Sciences (Belgrade), 2009)
Titration acidity and content of total tannins in mass-market red wines are analyzed in this paper. The content of total acids in wine, expressed through wine acid, was analyzed by potentiometric titration on 7.00 pH value. According to titratable acidity in analyzed wines, all wines (only) with analyzed parameters according to Regulations about wine quality. The analysis of differential potentiometric curves shows that these curves can give the answer to the question if non organic substances, amino groups and phenols are present in wine in large quantity, as they are always present in wine. However it doesn't give the clear answer which substances are present in analyzed samples. The answer to this question can be received only by the method of ionic chromatography. The content of total tannins shows short time of storage in wine cellars so wine wasn't stored long enough, i.e. they are commercial wines made for mass market production and consumption. Although they have less content of total tannin materials of given values, wine taste gives the correlation with other polyphenol materials that only give odour, aroma and 'bouquet' to wine. The relative error of mean value is very low which indicates the reproduction of results and reliability of the method of determination of total tannins in red wine.